Does Cultural Difference Affect Investment–Cash Flow Sensitivity? Evidence from OECD Countries. (28th February 2020) - Kashefi‐Pour, Eilnaz; Amini, Shima; Uddin, Moshfique; Duxbury, Darren
Abstract: We investigate the influence of national culture on corporate investment–cash flow sensitivity. We conjecture that national culture shapes managerial perceptions of information asymmetry and agency problems, thus impacting the investment–cash flow relationship. We document empirical evidence in support of our claim. By linking the investment–cash flow sensitivity to cultural differences, our findings show that, while collectivism has an attenuating influence, uncertainty avoidance, power distance and masculinity have a reinforcing effect on the relationship between cash flow and investment. Our results hold for a sample of 205, 268 firm‐years across 24 OECD countries between 1990 and 2017, and are robust after accounting for alternative statistical approaches, sample compositions and measures of cultural dimensions, along with controls for institutional and governmental factors. In addition, by decomposing cash flow into uses and sources of funds in a dynamic multi‐equation model, where firms make financing and investment decisions jointly subject to the constraint that sources must equal uses of cash, we find that national culture shapes how firms react to changes in cash flow.